Anticipare il Futuro della Cina. L’eredità del vescovo gesuita Jin Luxian SJ (“Anticipating the Future of China. The Heritage of the Jesuit Bishop Jin Luxian SJ”) - Rothlin, Stephan (La Civiltà Cattolica, 2020)

Un nuovo paradigma economico.(“Ideas for a New Economic Paradigm”) - Rothlin, Stephan (La Civiltà Cattolica, 2021)
La crisi del Covid-19 ha evidenziato il disagio e il divario sempre più ampio tra ricchi e poveri. La crisi finanziaria del 2007-2009 era già risuonata come un campanello d'allarme sulla necessità di

Professional Ethics as Training in Civic Education - Rothlin, Stephan (Hong Kong Journal of Catholic Studies, 2018)

Triggering a Change of The Economic Paradigm - Rothlin, Stephan (The Journal of the Macau Ricci Institute, 2021)

Pekinger Nachtgespräche: Gott und die Welt in China (Nighttalks in Beijing. God and the World in China) - Rothlin, Stephan; Achten, Peter (Fromm Verlag, 2018)

La Dottrina Sociale della Chiesa in Cina. Un riferimento per l’etica degli affari (“Catholic Social Teaching in China. A reference for Business Ethics”) - Rothlin, Stephan (La Chiesa in Cina. Un future da scrivere, 2019)

The Long March toward Moral Leadership in Business - Rothlin, Stephan; McCann, D (Silliman Journal, 2018)

International Business Ethics: Focus on China - Rothlin, Stephan; McCann, Dennis (Springer-Verlag, 2016)
This book addresses an essential need felt by many who seek to promote best business practices in China and East Asia – namely the need for culturally appropriate instructional materials (basic information, case studies and ethical perspectives) that will allow managers and entrepreneurs to understand and embrace the challenge of moral leadership in business. In an era characterized by globalization and the increasing importance of the economies of China, India, Japan and SE Asia, international business ethics must reflect the concerns of the people living and working in this area, the moral and spiritual traditions that have nurtured them and their specific contributions to sustainable development. This book presents twenty important case studies, taken from newsworthy events of the past few years, in which Asians and others have attempted to respond to this challenge. Each case study has been selected and shaped in order to highlight various aspects of doing business in Asia, starting with basic principles and moving on to the specific responsibilities that businesses have towards their various stakeholders. The authors contend that the best way to appreciate the relevance of Asian moral and spiritual traditions is to determine their specific contribution to virtue ethics, where the ancient traditions of both East and West converge in their focus on the qualities of moral leadership that form the basis of best business practice. Exploring the case studies will enable readers to appreciate the continued relevance of these ethical perspectives in Asian business. Best business practice clearly involves learning to do business and playing the game according to the rules; but the necessity of playing by the rules is not likely to become clear until one takes up the path that leads to a virtuous life in business, developing a moral character chiefly based on integrity.

Catholic Orders as Efficient Institutions - Rothlin, Stephan; Frey, B. S (Lumen: A Journal of Catholic Studies, 2015)

Transparency: A Necessary First Step Toward an Ethic of Finance - Rothlin, Stephan; McCann, D; Myers, T (Silliman Journal, 2017)

Catholic social teaching and environmental responsibility - Rothlin, Stephan; McCann, Dennis (A planetary and global ethics for climate change and sustainable energy, 2016)

Responsible Entrepreneurship. How to Write a Business Plan (Chinese-English Version) - Rothlin, Stephan; Myers, T. A; Thompson, M (University of International Business and Economics Press, 2015)

International Business Ethics. What We Have Learnt by Focusing on China? - Rothlin, Stephan; McCann, Dennis (Eine Wirtschaft, die Leben fördert. Wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)